The reverse logistics operation of solid waste pos-consumption of electronic products for domestic use in Brazil - Alós, Jandir dos Santos; Milan, Gabriel Sperandio; Eberle, Luciene (Revista de Administração da UFSM, 2023)
Purpose: The general objective of this research is to present a framework aimed at structuring the operation of the RLS – Reverse Logistics System in the context of the post-consumer solid waste of products electrical and electronics segment in Brazil. Design/Methodology/Approach: Exploratory research qualitative, operationalized through individual interviews with a semi-structured approach, with fourteen respondents, in addition to documentary research. Findings: The cost for the operation of this structure must also be treated as a critical point for the success of this system, mainly due to the lack of a vision focused on the circular economy of EEE – Electrical Equipment and Electronics. Implications for theory and practice: The study addressed some research gaps in relation to post-consumer reverse logistics. Regarding practical implementations, the development of a framework for the operacionalization of RLS stands out, and the evidence of this research concerns the lack of alignment, on the part of manufacturers and importers on issues related to EEE reverse logistics issues. Originality/Value: An emphasis on an advanced view of how to treat the solid waste consumer electronics segment (EEE) in Brazil.